Familial focal segmental glomerulosclerosis associated with a WT1 gene missense mutation: a case report - Ko, Yun Jung; Rhie, Seonkyeong; Baek, Jihyun; Seo, Go Hun; Lee, So-Young (Journal of the Pakistan Medical Association, 2023)
Focal segmental glomerulosclerosis (FSGS) can cause proteinuria and loss of kidney function, leading to end-stage renal disease (ESRD). Podocyte injury is the central pathophysiological mechanism of hereditary FSGS. Numerous mutations in genes encoding or affecting the transcriptional regulation of podocyte cell compartments have been detected in patients with genetic FSGS. Herein, we report a rare case of familial FSGS with an autosomal dominant WT1 mutation. A 63-year-old man developed proteinuria; his reading showed over 1g protein/day. A pathological diagnosis of FSGS was made after renal biopsy. His elderly brother and a 36-year-old son also had ESRD. Heterozygous variant of WT1 (NM_024426.4) c.1373G>A (p.Arg458Gln) missense was detected in the patient and his son, by whole-exome sequencing. Although genetic screening is not a part of routine practice, it should be performed in such cases to aid appropriate treatment options selecting, revealing extrarenal symptoms, and family planning.